CO2 emissions in German, Swedish and Colombian manufacturing industries (2013)
This study evaluates and compares the trends in CO2 emissions for the manufacturing industries of three countries: two developed countries (Germany and Sweden) that have applied several measures to promote a shift towards a low-carbon economy and one developing country (Colombia) that has shown substantial improvements in the reduction of CO2 emissions. This analysis is conducted using panel data cointegration techniques to infer causality between CO2 emissions, production factors and energy sources. The results indicate a trend of producing more output with less pollution. The trends for these countries' CO2 emissions depend on investment levels, energy sources and economic factors. Furthermore, the trends in CO2 emissions indicate that there are emission level differences between the two developed countries and the developing country. Moreover, the study confirms that it is possible to achieve economic growth and sustainable development while reducing greenhouse gas emissions, as Germany and Sweden demonstrate. In the case of Colombia, it is important to encourage a reduction in CO2 emissions through policies that combine technical and economic instruments and incentivise the application of new technologies that promote clean and environmentally friendly processes. © 2013 The Author(s).